TWO’S COMPANY - UNEXPECTED MEN 2 PRESENTING AS INCIDENTALOMA - Tan, Jie En; Tan, Florence Hui Sieng; Kuan, Yueh Chien; Chan, Pei Lin (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Bilateral pheochromocytomas are uncommon, classically described as occurring in 10% of cases. Such presentation should raise suspicion of the presence of a hereditary syndrome or predisposing genetic mutations. CASE A 43-year-old female presented with renal colic. A computed tomography scan showed nonobstructing renal calculi and bilateral adrenal incidentaloma measuring 3.8 cm. Serum calcium was normal (2.16 mmol/L). Twenty-four-hour urinary metanephrines were elevated sevenfold above normal with normal normetanephrines. Physical examination was unremarkable except for labile blood pressure (SBP 135-170 mmHg). She only reported symptoms of occasional palpitations and mild headache. Family history was significant for the death of unknown cause of her mother and 2 elder siblings before the age of 60 years. MEN 2A was suspected. Ultrasound of the neck revealed four TIRADS-5 thyroid nodules measuring 0.7- 1.3 cm, FNAC confirmed medullary thyroid carcinoma (MTC). Carcinoembryonic antigen was 13.6 ng/ml (<5). She underwent bilateral retroperitoneoscopic adrenalectomy uneventfully following adrenergic blockade. Postoperatively, she was normotensive and received hydrocortisone and fludrocortisone replacement. Histopathological examination confirmed bilateral pheochromocytoma with no malignant features. She awaits total thyroidectomy. Her kindred were advised to undergo screening for MEN 2, albeit the lack of genetic study due to financial constraints. CONCLUSION Genetic testing for RET proto-oncogene would be useful to guide management and screening in MEN 2. Medullary thyroid carcinoma is the most common manifestation of MEN 2 with 100% penetrance and should be actively sought for in patients suspected of having MEN 2.